Social Cognition and Friendships in Adolescents With Autistic-Like Experiences and Psychotic-Like Experiences - Sijtsma, Hester; Lee, Nikki C.; Hollarek, Miriam; Walsh, Reubs J.; van Buuren, Mariët; Braams, Barbara R.; Krabbendam, Lydia (Frontiers in Psychiatry, 2021)
Autism spectrum conditions (ASC) and schizophrenia spectrum conditions (SSC) are both characterized by changes in social-cognitive functioning. Less is known about the overlap and the differences in social-cognitive functioning when comparing individuals with subclinical levels of ASC and SSC, while studies in non-clinical samples have the benefit of avoiding confounds that are present in clinical groups. Therefore, we first examined how autistic-like experiences, positive psychotic-like experiences and the co-occurrence of both correlated with the performance on an extensive battery of social cognition tasks in young adolescents. Second, we examined the effect of autistic-like experiences, psychotic-like experiences and their co-occurrence on friendships in daily life. A total of 305 adolescents (Mage=12.6, sd=0.4, 147 boys) participated in the current study. A battery of social cognition tasks, comprising the Reading the Mind in the Eyes task, Dot perspective task and trust game were individually administered in a classroom setting, along with a friendship peer nomination questionnaire. Results indicated no evidence for a relationship between the performance on the social cognition battery and subclinical experiences of autism and/or psychosis. However, results did show that the amount of autistic-like experiences of adolescents were associated with being less often selected as a friend by their peers. By contrast, no relationship between self-reported friendships and autistic-like experiences was found. Neither a relationship between friendships and psychotic-like experiences was reported. This study provides initial evidence that information provided by peers may shed light on (altered) social behavior associated with autistic-like experiences that is not apparent on performance measures, as well as elucidate possible differences between autistic- and psychotic-like experiences.